2003
DOI: 10.1021/la035657n
|View full text |Cite
|
Sign up to set email alerts
|

Selective Noncovalent Adsorption of Protein to Bifunctional Metallic Nanowire Surfaces

Abstract: Metallic nanowires composed of nickel and gold as well as bimetallic nickel-gold nanowires were fabricated via templated electrodeposition in nanoporous alumina membranes. Gold surfaces were functionalized with alkanethiols with terminal hexa(ethylene glycol) groups (EG6), while nickel surfaces were functionalized with palmitic acid, a 16-carbon fatty acid. When exposed to a fluorescently tagged protein, hydrophobic nickel wires exhibited bright fluorescence while EG 6-terminated gold wires did not, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 27 publications
1
43
0
3
Order By: Relevance
“…In another example, nickel-gold nanowires were differentially functionalized by palmitic acid and hexa(ethylene glycol) terminated long chain thiol [118]. Gold surfaces were functionalized with alkanethiols with terminal hexa(ethylene glycol) groups (EG6), while nickel surfaces were functionalized with palmitic acid.…”
Section: Metallic Nanowiresmentioning
confidence: 99%
“…In another example, nickel-gold nanowires were differentially functionalized by palmitic acid and hexa(ethylene glycol) terminated long chain thiol [118]. Gold surfaces were functionalized with alkanethiols with terminal hexa(ethylene glycol) groups (EG6), while nickel surfaces were functionalized with palmitic acid.…”
Section: Metallic Nanowiresmentioning
confidence: 99%
“…In their study, they found sequential electro-deposition of gold and platinum metals in the pores of porous alumina membrane. Towards this end, amendments in the surface of nickel and gold nanowires results in selective adsorption of proteins (Birenbaum et al 2003;Gao et al 2007). These observations were further elaborated by demonstrating bifunctional and differential protein adsorption in bimetallic nickel and gold nanowires, for the same but hybrid and much stable nanowired structure towards biological molecules (Birenbaum et al 2003).…”
Section: Gold Nanowiresmentioning
confidence: 99%
“…Häm-IX-Porphyrin. In einer weiteren Untersuchung wies die gleiche Arbeitsgruppe nach, [103] dass IgGProtein aus Mäusen und dessen Antikörper selektiv auf Palmitinsäure-Monoschichten auf der Ni-Komponente eines Au-Ni-Stabs adsorbieren. Im Anschluss an eine derartige Funktionalisierung von Mehrkomponenten-Nanostäben konnten weitere selektive Umwandlungen auf den Monoschichten vorgenommen werden (Amid-, Thioharnstoff-und Thioetherkupplungen).…”
Section: Oberflächenmodifizierungunclassified